Accent imitation positively affects language attitudes - Adank, Patti; Stewart, Andrew J.; Connell, Louise; Wood, Jeffrey (Frontiers in Psychology, 2013)
People in conversation tend to accommodate the way they speak. It has been assumed that this tendency to imitate each other’s speech patterns serves to increase liking between partners in a conversation. Previous experiments examined the effect of perceived social attractiveness on the tendency to imitate someone else’s speech and found that vocal imitation increased when perceived attractiveness was higher. The present experiment extends this research by examining the inverse relationship and examines how overt vocal imitation affects attitudes. Participants listened to sentences spoken by two speakers of a regional accent (Glaswegian) of English. They vocally repeated (speaking in their own accent without imitating) the sentences spoken by a Glaswegian speaker, and subsequently imitated sentences spoken by a second Glaswegian speaker (order counterbalanced across participants). After each repeating or imitation session, participants completed a questionnaire probing the speakers’ perceived power, competence, and social attractiveness. Imitating had a positive effect on the perceived social attractiveness of the speaker compared to repeating. These results are interpreted in light of Communication Accommodation Theory.